Analisis Persepsi Pengguna Media Sosial Tentang Pembelajaran Online dan Offline Sebagai Kajian Desain Pembelajaran Blended yang Efektif dan Berkualitas - Sabon, Yuliana Olga Siba; Rahim, Abdul; Yansa, Hajra; Alfansuri, Dite Umbara; Lima, Cristina Normalita de; Lismawati, Dewi Astuti; Marlissa, Damaris (Indo-MathEdu Intellectuals Journal, 2024)
This research was conducted with the aim of examining the perception of twitter or X users about online and offline learning as a basis for considering blended learning design. The research was carried out using the Atlas.ti rocky thematic analysis approach. The stages of thematic analysis are data collection, category construction, sorting categories and data, naming categories, and finding meaning in each stage of analysis. The results of the study show that there are four groups of perceptions among students regarding the learning method they want: (1) students who prefer online learning, (2) students who prefer face-to-face learning, (3) students who are neutral, and (4) students who want a combination of online and face-to-face learning. Some of the factors that affect this perception include physical, psychological, and convenience factors offered by each learning method. This study also found a tendency to change perceptions among students. In order for online learning to provide optimal results, several important conditions are needed, namely guaranteed learning quality, student readiness to participate in learning independently and responsibly, and adequate online learning facility support